Intership supervisor selection using genetic algorithms - Karim, Junaida (2015)
Supervisor selection is a frequently task found among the committee or management group in several organization. The selection tasks will be prepared at accordance times with the proper listing at particular event or duration. Indirectly, the organization of committee or management group will be more efficient; well organized and manageable. In this study, Fakulti Teknologi Maklumat Dan Komunikasi (FTMK) at Universiti Teknikal Melaka Malaysia (UTeM) was chosen to be the case study for the researcher to test the genetic algorithm based on the criteria used by the faculty. From the investigation the internship supervisor selection can be defined as forming the allocation supervisor to the internship student from the FTMK with certain constraints to be satisfied. By using genetic algorithm approach, the priority factors for the assigning faculty supervisor to internship student has been identified and also development model of selection has been done to fulfill the criteria for the selection specified by the FTMK. Experimental results from the model selection output can used to verify with an actual data on selection of internship supervisor in FTMK, UTeM.